How and why will the oil refining industry change in the EEA until year 2025 Will these changes influence the demand of intermediate tankers? - Andersson, Marcus (My University, 2016)
The oil refining industry in the EEA faces future challenges. Some of these challenges are competition from non-EEA refiners, increased import of petroleum products to the EEA and unsophisticated technology of existing refineries. If the oil refining industry in the EEA will change in the future, what impact will these changes have on the intermediate product tanker segment trading in the EEA? These possible future changes in the refining industry are essential for ship-owners’ decision making in regards to efficient operation of intermediate product tankers in the EEA. The purpose of this study is to investigate how and why the oil refining industry in the EEA will develop until year 2025 and how these changes will affect the intermediate product tanker segment. To fulfil the purpose, a case study has been performed. The primary information for this study has been retrieved by conducting ten interviews with semi-structured questions. The result from this study shows that the refining industry in the EEA faces several future challenges. Increased competition from non-EEA refiners and increased import of petroleum products have been highlighted as the main challenges for the refining industry in EEA. This study also shows that the intermediate product tankers still are expected to be needed for regional transportation within the EEA. However, the intermediate product segment faces competition from larger segments and therefore it is important that the segment keeps its flexibility compared to larger segments to not lose its market shares. The size of existing intermediate product tankers is appropriate and therefore the size should retain in order to keep the segment´s flexibility.
Keywords: Transport; Transportteknik och logistik; Transport; Transport Systems and Logistics